2019
DOI: 10.3390/ijerph16173135
|View full text |Cite
|
Sign up to set email alerts
|

Walkability, Overweight, and Obesity in Adults: A Systematic Review of Observational Studies

Abstract: We conducted a systematic review to describe and summarize possible associations between the walkability index, overweight, and obesity. Systematic searches using seven electronic databases and reference lists were conducted to identify papers published until December 2017. Observational studies, describing associations using regression-based statistical methods, published in English and Portuguese, reporting markers of overweight and obesity, and involving adults (≥18 years) were included. Of the 2469 referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…A recent review of studies on neighborhood walkability and obesity among adults in high-income countries found cross-sectional study designs made up the majority of studies reporting an inverse relationship between objective walkability indices and markers of overweight/obesity [ 5 ]. No longitudinal studies in the review reported significant findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of studies on neighborhood walkability and obesity among adults in high-income countries found cross-sectional study designs made up the majority of studies reporting an inverse relationship between objective walkability indices and markers of overweight/obesity [ 5 ]. No longitudinal studies in the review reported significant findings.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this finding, Chandrabose et al [ 6 ] highlight the strength of association is weakened (though remains statistically significant) in studies of objective walkability. Although these two reviews differ in purpose and article inclusion criteria, both reviews emphasize the need for stronger longitudinal designs and methodologies to advance neighborhood walkability and obesity research [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, not for all built environmental features positive associations were found, which limits the evidence 15 16 and indicates that different environmental features could have different associations with walking on the one and cycling on the other hand. 12 Additionally, although many studies on walkability and BMI indicate that BMI is lower the better walkability is, [17][18][19][20] there are also studies that did not found any or only very weak associations between BMI and walkability. [21][22][23] These inconsistencies could be due to the heterogeneity of walkability measures and methods used.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] These inconsistencies could be due to the heterogeneity of walkability measures and methods used. 22 23 Moreover, most studies used self-reported measures of weight and height, 17 resulting in a BMI that tends to be lower than the actual BMI. 24 25 Additionally, inconsistencies of the current findings may in part be due to little variability of walkability measures in some singlesite studies, which limits the generalisability of current results.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have also been studies that did not find associations between neighborhood characteristics and BMI in older adults (Michael et al, 2013). Thus, neighborhood attributes may affect an individual’s exercise, eating habits and BMI; however, more research is needed (Ding & Gebel, 2012; Paulo Dos Anjos Souza Barbosa et al, 2019). These findings suggest that future research should consider additional neighborhood characteristics relevant to older adults, which this study aims to do.…”
mentioning
confidence: 99%